THEOLOGICAL AND PSYCHOLOGICAL STUDIES: THE FINAL DESTINATION OF DEAD BABIES AND THE IMPLICATIONS FOR THE NIAS ISLANDS LUTHERAN CONGREGATION - Fenius Gulo; Raisa Fransiska Maria (Manna Rafflesia, 2024)
The death of babies on the Nias Islands, where most of the population adheres to Lutheran Christian beliefs, has become a serious problem from a theological and psychological perspective. Theologically, congregations are confused about the certainty of their baby's destination or safety when they die. The state of grief and confusing doctrines about soteriology related to dead babies have intimidated the psychology of parents whose children died as babies. To overcome this problem, researchers conducted a study using qualitative research methods. Based on theological investigation, the destination of a baby's death depends on the will of God, who is abundant in grace. He was able to choose someone to save from the womb. Meanwhile, from a psychological perspective, it is denied that parents whose babies die experience psychological disorders. Theological and psychological studies regarding the final destination of dead babies for the Nias Islands Lutheran congregation are the novelty of this research.